The role of natriuretic peptides in volume assessment and mortality prediction in Haemodialysis patients - Sivalingam, Murugan (BMC Nephrol, 2015)
BACKGROUND: Maintaining optimal fluid balance is essential in haemodialysis (HD) patients but clinical evaluation remains problematic. Other technologies such as bioimpedance are emerging as valuable adjuncts. This study was undertaken to explore the potential utility of the natriuretic peptides – atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) in the assessment of fluid status and cardiovascular risk in this setting. METHODS: This was a cross-sectional study carried out in an unselected cohort of 170 prevalent HD patients. Volume status was assessed by clinical parameters – the presence or absence of peripheral oedema, raised jugular venous pressure and basal lung crepitations; by extracellular fluid volume (ECFV) status determined by whole body bioimpedance; and by serum levels of BNP and ANP (pre- and post –dialysis). The relationships of ANP and BNP levels to clinical and bioimpedance parameters of volume status was determined. Patients were followed up for 5 years to assess the relationship of natriuretic peptide levels to mortality. RESULTS: Bioimpedance estimates of ECFV expansion (>105 % of ideal ECFV) was present in 52 % of patients pre-dialysis. A significant proportion (21 %) of pre-dialysis patients had a depleted ECFV (<95 % of ideal ECFV) pre-dialysis. The situation was reversed post-dialysis. A raised JVP >3 cm was the most reliable clinical sign of ECFV expansion inferred from bioimpedance measurements and natriuretic peptide levels. The vast majority of patients with this sign also had lung crepitations or peripheral oedema or both. BNP was a stronger predictor of ECFV expansion than either pre- or post-dialysis ANP. BNP was also a stronger predictor of five-year survival. CONCLUSION: Serum levels of BNP have a strong relationship to both volume status and survival in HD patients. We found no clear role for measurement of ANP, though changes in blood levels may be a sensitive indicator of acute changes in volume status. Whether monitoring levels of these peptides has a role in the management of volume status and cardiovascular risk requires further study.